The development discourse and education in the contemporary time. Is training in sciences relevant? - Serrato Rodríguez, Deysi (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This article is constituted on the basis of findings from the research project Potential conditions in teaching of biology in contemporary Colombian schools: a pedagogical strategy for the political discussion on its displacement, which corresponds to the focus of research Routes and Events from the Department of Biology at Universidad Pedagógica Nacional in Colombia. The aim is to highlight how the development discourse settles in the education field as a strategy to make feasible training processes in sciences and its relations with permanent learning, human capital, and research. From an archaeological and genealogical perspective, three methodological concepts are discussed: knowledge, power, and subjectivation. Lastly, it is found that training through which is contemporary is related to flexibility and skills acquisition in favor of the construction of knowledge representing an economic benefit in which science plays a predominant role.